2014
DOI: 10.1152/ajplung.00077.2014
|View full text |Cite
|
Sign up to set email alerts
|

Claudin 4 knockout mice: normal physiological phenotype with increased susceptibility to lung injury

Abstract: Claudins are tight junction proteins that regulate paracellular ion permeability of epithelium and endothelium. Claudin 4 has been reported to function as a paracellular sodium barrier and is one of three major claudins expressed in lung alveolar epithelial cells (AEC). To directly assess the role of claudin 4 in regulation of alveolar epithelial barrier function and fluid homeostasis in vivo, we generated claudin 4 knockout (Cldn4 KO) mice. Unexpectedly, Cldn4 KO mice exhibited normal physiological phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 84 publications
4
63
0
Order By: Relevance
“…Previous studies have shown that constitutive Cldn1 inactivation in mice results in perinatal death due to loss of epidermal TJ integrity (23), while CLDN4 is also expressed in kidney and lung, and constitutive or conditional Cldn4 inactivation has been linked to urothelial hyperplasia and hydronephrosis (53), failure of chloride reabsorption (54), and susceptibility to lung injury (33). Our results thus suggest that the BBB and GL represent a coordinated double barrier to CNS entry.…”
Section: And E) In Contrast Lesions In Mgfapcre Cldn4supporting
confidence: 56%
“…Previous studies have shown that constitutive Cldn1 inactivation in mice results in perinatal death due to loss of epidermal TJ integrity (23), while CLDN4 is also expressed in kidney and lung, and constitutive or conditional Cldn4 inactivation has been linked to urothelial hyperplasia and hydronephrosis (53), failure of chloride reabsorption (54), and susceptibility to lung injury (33). Our results thus suggest that the BBB and GL represent a coordinated double barrier to CNS entry.…”
Section: And E) In Contrast Lesions In Mgfapcre Cldn4supporting
confidence: 56%
“…Our data suggest that retention of claudin-4 alone is not sufficient to support normal lung epithelial barrier function. Consistent with this observation, claudin-4-deficient mice have a relatively mild lung phenotype (23). Moreover, claudin-4 upregulation does not rescue the decrease in AEC barrier function found in claudin-18 knockout mice (31,32).…”
Section: Discussionmentioning
confidence: 78%
“…Within the alveolus, claudin-4 is expressed by both type I and type II pneumocytes [38]. The importance of claudin-4 in lung function is demonstrated by the fact that claudin-4 knockout mice display increased permeability to 5-carboxyfluorescein and decreased alveolar fluid clearance [39]. In vitro, the transduction of cells with claudin-4 increased the TER by ∼50% [40].…”
Section: Discussionmentioning
confidence: 99%